Chemodiversity, Biological Activities and Molecular Docking Studies of Leptadenia pyrotechnica (Forssk.) Decne: A Comprehensive Approach to Validate Its Medicinal Use. Issue 5 (29th March 2022) - Zubair, Momina; Nazir, Mamona; Saleem, Muhammad; Raiz, Naheed; Touseef, Saba; Khan, Saima; Zengin, Gokhan; Ehsan Mazhar, Muhammad; Imran Tousif, Muhammad
Abstract: Leptadenia pyrotechnica (Forssk.) Decne is growing in Cholistan desert, and is known for its laxative, analgesic, anabolic and astringent, antioxidant, anti‐inflammatory, antibacterial, antitumor, hypolipidemic and antiatherosclerotic properties. The present study disclosed the metabolic picture of L. pyrotechnica and validates its folk uses. LP‐H fraction constitute 25.79±0.11 mgGAE/g extract and 20.64±0.33 mgRE/g extract of phenolic and flavonoid content, respectively, followed by LP‐E (23.15±0.33 mgGAE/g extract and 19.40±0.13 mgRE/g extract), however, LP‐E exhibited the highest free radical scavenging (DPPH: 21.05±0.45mgTE/g and ABTS: 68.12±0.53 mgTE/g) and metal reducing (FRAP: 44.93±1.66, CUPRAC: 117.42±1.28 mgTE/g, respectively) activities. The total antioxidant capacity in Phosphomolybdenum assay (1.52±0.14 mmolTE/g) and ferrous ion chelating (11.57±0.29 mgEDTAE/g) activities were observed highest for LP‐H extract. In cholinesterase's inhibitory assays, the LP‐E and LP‐W extracts exhibited inhibitory values as 2.43 and 2.40±0.07 mgGALAE/g extract, respectively against AChE, while against BChE the LP‐H displayed the highest value as 5.98±0.44 mgGALAE/g extract. The LP‐H fraction also showed the highest inhibition potential (7.72±0.14 mmol ACAE/g and 0.55±0.01 mmol ACAE/g, respectively) against α‐glucosidase and α‐amylase enzymes, while, in tyrosinase inhibitory assay, all the fractions exhibited significant activities in the range of 59.35±0.29 to 55.18±0.49 mgKAE/g extract. RP‐UHPLC/MS analysis of LP‐M disclosed the presence of 57 metabolites of various classes. A multivariate analysis and molecular docking study was also carried out to establish relationships between the metabolites and the biological activities, which finally validate the use of L. pyrotechnica as herbal medicine or component nutraceutical, food and cosmetic industry. Abstract :